Galectin-8 deficiency promotes chronic splenomegaly persistence in Chagas disease - Bertelli, Adriano; Saborit, Juan Ignacio; Beccaria, Cristian Gabriel; Vanagas, Laura; Angel, Sergio Oscar; Campetella, Oscar; Gruppi, Adriana; Leguizamón, María Susana (Frontiers in Cellular and Infection Microbiology, 2025)
Galectins (Gals) are mammalian lectins with affinity for β-galactosides, which drive the immune response through several mechanisms. The specific role of Gal-8 in the development of inflammation remains controversial, as it has been shown to induce either T cell proliferation or regulation in different models. During the acute phase of Trypanosoma cruzi infection, a characteristic splenomegaly is induced that is associated with both antigen-specific and non-specific polyclonal lymphocyte proliferation. This splenomegaly resolves as the infection transitions to the chronic phase. While the pathogenesis of Chagas disease is not yet fully understood, it is widely accepted to involve both parasite persistence and the host immune response. In this study, C57BL/6J and Gal-8-deficient (KO) mice infected with the Ac strain were analyzed during the chronic phase (4 months post-infection). Notably, infected Gal-8KO mice failed to resolve the T. cruzi-induced acute phase splenomegaly. Despite this, parasitemia, spleen parasite load, and survival rates were comparable between the two groups, suggesting that Gal-8 is not involved in parasite control. The observed differences in spleen cellularity were primarily attributed to T lymphocyte proliferation, while B cells exhibited no significative changes in total cell number, proliferation levels and production of total and parasite-specific antibodies. Overall, our results reveal that Gal-8 plays an anti-inflammatory role during chronic T. cruzi infection and is critical in controlling splenomegaly, a process for which no associated regulatory molecules have been identified to date.